Handbook of Green computing and blockchain technologies - Saini, Kavita 1976-; Khari, Manju (Green engineering and technology: concepts and applications, 2022)
This handbook provides a computational perspective on Green Computing and Blockchain Technologies. It presents how to not only identify challenges using a practical approach but how to also develop strategies for addressing industry challenges. Handbook of Green Computing and Blockchain Technologies will have a practical-oriented approach, include solved examples, highlighting standardization, industry bodies, and initiatives. Case studies are included for a deeper understanding of Blockchain and are related to real-time scenarios. The book will analyze the current research and development in Green Computing and Blockchain analytics, study the existing related standards and technologies, and provide results on implementation, challenges, and issues in today’s society. Those that will benefit from this handbook include researchers, software developers, both undergraduate and postgraduate students in Industrial Systems, Manufacturing, Information Technology, Computer Science, Manufacturing, Communications, and Electrical Engineering